Analysis of Mathematical Communication Ability of Grade X Students of SMK Tiara Bangsa Bekasi on the Material of Linear Equation Systems of Two Variables - Kasih Haryo Basuki; Della Suci (PT FORMOSA CENDEKIA GLOBAL, 2024)
Mathematical communication skills are one of the important competencies that students need to have to understand and apply mathematical concepts. This study aims to analyze the mathematical communication skills of class X students of SMK Tiara Bangsa Bekasi on the material of Two-Variable Linear Equation System (SPLDV). The research method used is descriptive with a quantitative approach. Data were collected through mathematical communication skills tests, observations, and interviews. The results of the study showed that the mathematical communication skills of class X students of SMK Tiara Bangsa Bekasi on the SPLDV material were in the moderate category, this was indicated by the average value of students' mathematical communication skills as a whole was 63.21 and based on the level of mathematical communication of 28 class X students, there were 4 students with a high category with a percentage of 16%, 18 students with a moderate category with a percentage of 63%, and 6 students with a low category with a percentage of 21%. From these results, there are several aspects that need to be improved, such as understanding concepts and the ability to explain mathematical ideas orally and in writing